A contagious cause the American hunt for cancer viruses and the rise of molecular medicine - Scheffler, Robin Wolfe (The University of Chicago Press, 2019)
Is cancer a contagious disease? In the late nineteenth century this idea, and attending efforts to identify a cancer "germ," inspired fear and ignited controversy. Yet speculation that cancer might be contagious also contained a kernel of hope that the strategies used against infectious diseases, especially vaccination, might be able to subdue this dread disease. Today, nearly one in six cancers are thought to have an infectious cause, but the path to that understanding was twisting and turbulent. ​ A Contagious Cause is the first book to trace the century-long hunt for a human cancer virus in America, an effort whose scale exceeded that of the Human Genome Project. The government's campaign merged the worlds of molecular biology, public health, and military planning in the name of translating laboratory discoveries into useful medical therapies. However, its expansion into biomedical research sparked fierce conflict. Many biologists dismissed the suggestion that research should be planned and the idea of curing cancer by a vaccine or any other means as unrealistic, if not dangerous. Although the American hunt was ultimately fruitless, this effort nonetheless profoundly shaped our understanding of life at its most fundamental levels. A Contagious Cause links laboratory and legislature as has rarely been done before, creating a new chapter in the histories of science and American politics.